Sentry 'towers' of Isfijab in archaeological cartography - B.A. Baitanayev; M.A. Antonov; A.A. Yergeshbayev; A.Kh. Shayakhmetov (Ученые записки Казанского университета: Серия Гуманитарные науки)
The mapping data based on earlier archaeological surveys with the use of modern GIS technologies were presented. A database with archaeological data on the monuments typologically related to Karaultobe and settlement monuments of the early-medieval period of the Isfijab historical and cultural district was compiled. The data under study are mostly the results of explorations and surveys of monuments such as Karaultobe. The analysis was performed with the help of the ArcGIS mapping software. The geographical coordinates of each Karaultobe and the altitude map were used separately. The geographical points is a set of data obtained using GPS during the field research (archaeological explorations in particular). The altitude map is high-resolution radar data available on the US Geological Survey website. A digital map with data on the visibility of the chains of monuments and their functioning in the settlements of the region was created. The maps were created not only for publishing data in various formats and for navigation, but also for works that include displaying study analyses as a database. The aim of the project is to create a series of maps: the main map, where all objects are displayed, as well as a number of detailed maps of certain regions and maps with the results of the landscape analysis. In this paper, only some maps – small with simplified annotations – were used.